2019
DOI: 10.1186/s12862-019-1431-2
|View full text |Cite
|
Sign up to set email alerts
|

Global phylodynamic analysis of avian paramyxovirus-1 provides evidence of inter-host transmission and intercontinental spatial diffusion

Abstract: Background: Avian avulavirus (commonly known as avian paramyxovirus-1 or APMV-1) can cause disease of varying severity in both domestic and wild birds. Understanding how viruses move among hosts and geography would be useful for informing prevention and control efforts. A Bayesian statistical framework was employed to estimate the evolutionary history of 1602 complete fusion gene APMV-1 sequences collected from 1970 to 2016 in order to infer viral transmission between avian host orders and diffusion among geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…The deduction was further supported by the migration link from Europe to East China in the diffusion processes of VI.2.1.1.2.2 PPMV-1. Previous studies demonstrated that the European continent was the epicenter of global dissemination of PPMV-1 due to the movement of pigeons [39,40]. Cai et al [16] also proved that the VI viruses (P4 and W4) of China originated in Europe.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The deduction was further supported by the migration link from Europe to East China in the diffusion processes of VI.2.1.1.2.2 PPMV-1. Previous studies demonstrated that the European continent was the epicenter of global dissemination of PPMV-1 due to the movement of pigeons [39,40]. Cai et al [16] also proved that the VI viruses (P4 and W4) of China originated in Europe.…”
Section: Discussionmentioning
confidence: 98%
“…Sampling bias is an important factor that should also be considered in models. Hicks and his coworkers used the tip swap analysis to assess the impact of sampling on the estimated viral diffusion patterns of avian paramyxovirus-1 and found that the sample was biased toward the presence of earlier sequences within the dataset [40]. In this study, we compared the Bayesian analysis results with those from 10 replicate datasets in which the location states were randomized among the sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the historical spread exhibited by other animal diseases, such as Foot and Mouth Disease (Bachanek-Bankowska et al, 2018) or Avian avulavirus (Hicks et al, 2019), EIAV has shown the ability to spread rapidly through long distances, with evident jumps across continents. Spatiotemporal patterns of EIAV visualized through skyline plot showed that its worldwide spread have been accompanied by a constant increase in the genetic diversity that started around 1970 and ceased 20 years later, evidencing an abrupt decrease that could be explained by the intensification of disease control programs in countries with elevated count cases and the development of better ELISA-based EIAV serologic tests (Issel and Cook, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Phylodynamic models can be used to estimate the epidemiological and ecological characteristics of viral ancestors, allowing characterization and quantification of viral movements [ 42 ]. In this study, we conducted the first comprehensive phylodynamic study of genotype VII NDVs in China, indicating that East China was likely the origin of genotype VII NDVs in China.…”
Section: Discussionmentioning
confidence: 99%
“…Further, TMRCA of genotype VII NDVs was dated to the year 1951 (95% HPD: 1941–1960), well before the first genotype VII NDV sequence from China was submitted to the GenBank. Hicks et al [ 42 ] inferred that genotype VII NDVs migrated to South Asia, East Asia, and Africa from Southeast Asia and to the Middle East from East Asia, with TMRCA of 1940. A reasonable corollary to this would be that genotype VII NDVs emerged in South Asia in the 1940s and gradually spread to East Asia, including China.…”
Section: Discussionmentioning
confidence: 99%